PENGARUH HARGA, PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PASIEN MENEBUS RESEP DOKTER : STUDI KASUS PADAAPOTEK K-24 PURWOREJO (STIE Rajawali Purworejo, 2018)
This study aims to determine the Influence of Price, Service and Location on Decision of Patient Redeeming Prescription Doctor (Case Study At K - 24 Purworejo Pharmacy). Samples in this study are patients who redeem aprescription in pharmacy K-24 Purworejo more than 2x as many as 50 people . This research uses data analysis methods, multiple regression, coefficient of determination, t test and ftest. After doing research about the influence of price, service and location to decision of patient in redeeming prescription doctor (study of pharmacy K -24 Purworejo) hence obtained result as follows: There is partially positive influence and significant antaraharga to decision of patient redeem prescription doctor at pharmacy K-24 Purworejo with t count = 5,978 and p = 0,000 <0,05. There isinfluence secaraparsial and significant of service to decision of patient redeem prescription doctor at pharmacy K-24 Purworejo with t count = 7,939 and p = 0,000 <0,05. partially and significantly influence the location of the decision of the patient to redeem the prescription at the pharmacy K-24 Purworejo with tarithmetic = 1.552 and p = 0.127> 0.05.Ada there is a positive and significant influence simultaneously between price, service, and location to the decision the patient redeemed the prescription at K-24 Purworejo Pharmacy. Based on F value count = 44,982 and p = 0,000 <0,05. And the value of F table, then F arithmetic>F table (44,983> 2,807) or probability 0.000 <0,05 which means hypothesis four (H4) which states simul taneously there is a positive and significant influence influence price, service and location to the patient decision redeemed recipes accepted and HO rejected.